13 Validating the heart rate variability risk prediction model and accelerated diagnostic protocol (HRVPM-ADP) for chest pain patients at the ED. (26th April 2019) - Liu, Nan; Seow, Cui Shan; Koh, Zhi Xiong; Guo, Dagang; Lim, Swee Han; Hock Ong, Marcus Eng
Abstract : Background: Patients presenting to the emergency department (ED) with chest pain can have varying etiologies from benign musculoskeletal pain to life-threatening acute myocardial infarction. HRVPM-ADP 1 was previously derived as a non-invasive risk stratification tool for chest pain. We aimed to validate this novel triage method and compare it against the HEART score. Method: This study retrospectively analysed 545 chest pain patients presenting to Singapore General Hospital between January 2014 and June 2016. The primary outcome was 30 day major adverse cardiac events (MACE). HRV prediction model (HRVPM) was previously derived with 6 HRV and 3 ECG variables. Troponin results were then added to develop an accelerated diagnostic protocol (HRVPM-ADP). Performance of the HRVPM-ADP was validated and compared against the HEART score. Results: HRVPM had an AUC of 0.711 (95% CI 0.659, 0.763). This outperforms HEART with AUC 0.708 (95%CI 0.658, 0.758). HRVPM-ADP identified low risk chest pain with sensitivity of 98.5% (95%CI 96, 100) and negative predictive value (NPV) of 96.0% (95% CI 89, 100). In comparison, a low risk HEART score (0–3) had sensitivity of 94.8% (95%CI 89, 98) and NPV of 92.7% (95%CI 85, 97). Conclusion: HRVPM is a non-invasive risk stratification tool which has demonstrated comparable performance with the HEART and can be used as an ADP to identify low-risk chest pain patients in the ED who are safe for early discharge. Reference: Ting CE, et al . Heart rate variability and pre-hospital risk stratification of chest pain patients . European EMS Congress, Copenhagen, Denmark, April 2018. Conflict of interest: None. Funding: SingHealth Foundation Research Grant SHF/FG652P/2017.